KEDINAMISAN ANGGOTA KELOMPOK TANI DALAMBERUSAHATANI DI DESA BAUMATA TIMUR KECAMATAN TAEBENU KABUPATEN KUPANG - Frederikus Afeanpah; Ignatius Sinu; Selfius P. N. Nainiti (Undana Press, 2022)
This research was conducted at the Nekamese Farmer Group and the Independent Business of Baumata Timur Village, Taebenu District, Kupang Regency, from November to December 2020. This study aims to determine: 1) The level of dynamics of farmer group members in farming, 2) Factors that affect farmer groups in Bussiness. This research was conducted by survey method. The location of the research was determined purposively with the consideration that the Nekamese Farmer Group and the Mandiri business were farmer groups that were still active in East Baumata Village. The population in this study were all of the Nekamese Farmer Group and Independent Enterprises, which amounted to 30 people. The type of data collected is primary data obtained from direct interviews with respondents who are guided by the list of questions while secondary data is obtained through searching written documents, related agencies and literature related to research. To find out the first objective, the data were analyzed using a Likert scale, and to answer the second objective, the data were analyzed using the Sperman Rank statistical nonparametric test as follows: Analysis of the average and presentation. The results of this study indicate that: 1) The level of dynamics of the Nekamese Farmer Group and Independent Enterprises in East Baumata Village, Taebenu District, Kupang Regency is in the Not Dynamic category with an average score of 2.19 with a maximum percentage of 43.85%. The element that contributes the most to the dynamics of the farmer group is the element of group effectiveness with an average score of 43.85 and a percentage of 94%. The element that contributes the least to group dynamics is the element of group development with an average score of 2.5 and a percentage of 50%. 2) The factors faced by farmers in the Nekamese Farmer Group and Independent Enterprises, Taebenu District, Kupang Regency are inappropriate group functions and tasks so that the satisfaction of each group member is not achieved, the government's lack of attention and cooperation within the group.